SANKSI PENYEBAR HOAX PERSPEKTIF HUKUM PIDANA ISLAM - Wahyu Abdul Jafar (Faculty of Sharia (Islamic Law) at Fatmawati Sukarno State Islamic University Bengkulu, 2019)
This study discusses the issue of hoaxes which have been troubling the community. One reason for the rise of hoax news is that the handling is only from the side of positive law without involving religious elements, whereas religious teachings are very effective for preventive actions because if there are religious elements in the handling, people will always be watched and afraid of sinning if they violate. The subject of this study is how to set ta'zir sanctions for hoax makers and disseminators in the perspective of Islamic law. This study is included in the literature research category, while the approach used in this study is a normative approach. The data collection technique used is documentation technique. After an in-depth study was obtained a conclusion that there were three categories of ta'zir sanctions, namely minor, moderate and severe sanctions. Minor sanctions are given to perpetrators and disseminators of hoaxes with motives of ignorance and victims of technological and information developments. While giving sanctions is being given to the perpetrators and disseminators of the hoax with the motive for the absence of legal certainty. Then hoax makers and spreaders who have motives for malicious intentions and politics are given the heaviest sanctions